Theoretical analysis of tyre slip power dissipation mechanism using brush model. Issue 8 (2nd August 2020) - Kobayashi, Takao; Katsuyama, Etsuo; Sugiura, Hideki; Hattori, Yoshikazu; Ono, Eiichi; Yamamoto, Masaki
ABSTRACT: Tyre slip power loss has become a key issue for extending the number of miles per charge an electric vehicle can achieve. However, the definition and mechanism of tyre slip power loss has yet to be defined theoretically. Therefore, this paper analytically clarifies the energy equilibrium state when tyre forces are generated using a brush tyre model that is widely used in vehicle dynamics simulations. The analysis results show that input power is dissipated only in the sliding region, but that the amount of dissipation is equal to the total mechanical power including potential energy due to elastic deformation in the adhesion region. The consistency between the energy source and sink of vehicle-tyre dynamics was proved theoretically.